Growth of zinc sulfide by mist chemical vapor deposition depending on mist size and thermal conditions in susceptor. Issue 7 (14th April 2016) - Uno, Kazuyuki; Yamasaki, Yuichiro; Gu, Ping; Tanaka, Ichiro
Abstract: Zinc sulfide (ZnS) films were successfully grown by using mist chemical vapor deposition (mist‐CVD) with fine‐channel susceptor made of quartz. For the investigation of growth dynamics, two types of mist generators and two types of susceptors were prepared and distribu¬tion profiles of film thickness were examined. Thermal efficiency of susceptor depends on heat¬penetration efficiency and line‐velocity of the mists, which are influenced by the fine‐channel gap‐height of the susceptors. Using larger size of mists requires higher thermal efficiency in susceptor to obtain a flat thickness distribution. This result indicates that the optimization of the mist size and the susceptor structure is important for the film uniformity of grown films by the mist‐CVD. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)